Socialization of Increasing School Participation Rates in Sepuk Tanjung - Putri Tipa Anasi; Budiman Tampubolon; LM Hari Christanto; Nur Meily Adlika; Y. Touvan Juni Samodra (Universitas Tanjungpura, 2020)
Compulsory education has become a policy priority of the Indonesian Government. The Indonesian people still face educational problems, such as many dropouts and the discontinuation of education among the population aged 7-15 years. One of the problems of this education appeared in Sambas Regency. In Sepuk Tanjung Village in Sambas District, there is one elementary school in an oil palm plantation area with a decreasing number of students at each grade level. The school has the highest percentage of students in 1 to 4 grades. However, starting from 5 grade to 6 grade, the number of students has decreased because students in 5 grade and 6 grade have dropped out of school. Therefore, socialization is needed to increase the school participation rate. This school participation rate can increase, of course, starting from within the family. So that parents as guardians of students and teachers will be participants in this activity. This activity resulted in a discussion about the reasons for the low enrollment rates in this area. As well as suggestions for solutions in overcoming transportation access difficulties to higher-level schools based on the number of facilities and population of the area